Green synthesis and characterisation of antioxidant-tagged gold nanoparticle (X-GNP) and studies on its potent antimicrobial activity. Issue 1 (1st January 2018) - Bhattacherjee, Abhishek; Ghosh, Tanushree; Datta, Abhijit
ABSTRACT: Alternanthera philoxeroides (Mart.), a weed, mainly from tropical origin and easily available worldwide. People used to eat it as a food mainly in South Africa. In our previous report we have thoroughly characterise several important phenolics, monoterpene and phenylpropane from methanol soluble fraction of Alternenthera leaves (fraction X) and also reported their α-glucosidase inhibitory, antimicrobial and antioxidant activities. All these isolated natural compounds are well characterised and widely studied. In our present study we try to use this beneficial fraction (named fraction X) in green synthesis of gold nanoparticles (X-GNP). We also try to explore the beneficial aspects of green synthesis in comparison with commonly used chemical synthesis method (GNP) in context with their antimicrobial activity. UV/Vis spectroscopy, DLS, Zeta potential, FT-IR, EDAX and other microscopic techniques namely: SEM, AFM were used to characterise the synthesised nanoparticles. Different important microbial strains were used to evaluate the antimicrobial activity of prepared nanoparticles. Overall the studies suggest successful synthesis of green nanoparticles (X-GNP) and also showed the improvement in antimicrobial activity of X-GNP nanoparticles.